Goya - Wright, Patricia (New York : Dorling Kindersley, 2000)
A study of the art and life of the Spanish artist, and the influences that shaped his work.
Success in Saragossa -- Goya at thirty -- Tradition and invention -- Fashionable portrait painter -- Cartoons for two kings -- Goya and the child -- Sorcery and witchcraft -- The Royal family -- Majas and majismo -- The horrors of war -- Spanish rule restored -- Goya and the church -- Brush with death -- House of the deaf man -- The last years in Spain.
Includes index.
Book Report.
Kliatt.
7.1.
7.1
5-8
Keywords: Goya, Francisco, -- 1746-1828.; Goya, Francisco, -- 1746-1828.; Goya, Francisco, -- 1746-1828.; Artists -- Spain -- Biography; Artists -- Spain -- Biography; Artists -- Biography; Artists -- Spain -- Biography